PENGARUH EXPERIENTAL MARKETING, STORE ATMOSPHERE, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI ANGKRINGAN KENDI RENJANA KLATEN - Winda Rohmawati; Sarsono Sarsono; Fithri Setya Mawarti (JURNAL ILMIAH EDUNOMIKA, 2021)
Research was sought to examine marketing based on experience, storeiatmosphere, priceiand serviceiquality ofipurchasing decisionsiat Angkringan Kendi Renjana. Quantitative descriptive is used in this type of research. All consumers who make purchases at Angkringan Renjana are counted as samples in this research. Convience samplingiis used for respondent techniques, the number of samples obtained is 100 respondents. Inithis study,iusing multipleilinear regressionianalysis techniquesiSPSS 15. Theiresults of the description can be ignored from the marketing experience which hasia positiveiand significantieffect onipurchasing decisionsiin Angkringan Kendi Renjana. storeiatmosphere hasiapositive andisignificant effectionidecisions iniAngkringan Kendi Renjana. priceihas aipositive andisignificant effectionipurchasing decisionsiin Angkringan Kendi Renjana . service quality hasiaipositive effectand significantito theipurchase decisioniin Angkringan Kendi Renjana. Keywords: Experienta Marketing; Store Atmosphere; Price; Quality of Service; Purchasing Decision